2009
DOI: 10.1021/jf900363r
|View full text |Cite
|
Sign up to set email alerts
|

Folate Content in Tomato (Lycopersicon esculentum). Influence of Cultivar, Ripeness, Year of Harvest, and Pasteurization and Storage Temperatures

Abstract: The effects of cultivar, on-vine ripening, and year of harvest on the folate content of raw tomatoes were studied. Folate content in hot-break tomato puree (HTP) subjected to pasteurization at different temperatures and its evolution during the shelf life of tomato juice were also investigated. 5-Methyltetrahydrofolate (5-CH(3)-H(4)-folate) was the only folate compound identified in raw tomatoes and HTP, but tetrahydrofolate (H(4)-folate) was 10% of the folate detected in tomato juice. The content of folates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 29 publications
3
28
1
2
Order By: Relevance
“…Low dietary folate intake is related to low consumption of folate-rich foods, long storage of the folate-containing foods, and a reduction in vitamin content during food processing [57]. Mean folate intake in European populations ranges from 180 to 280 μg/day [5,29,139], which is not sufficient to prevent folate-responsive NTD cases.…”
Section: Strategies To Prevent Ntds By Improving Maternal Folate Statusmentioning
confidence: 99%
“…Low dietary folate intake is related to low consumption of folate-rich foods, long storage of the folate-containing foods, and a reduction in vitamin content during food processing [57]. Mean folate intake in European populations ranges from 180 to 280 μg/day [5,29,139], which is not sufficient to prevent folate-responsive NTD cases.…”
Section: Strategies To Prevent Ntds By Improving Maternal Folate Statusmentioning
confidence: 99%
“…Tomato product consumption in itself has been associated with a lower CVD risk, an effect generally attributed to antioxidant content, especially lycopene [24,25]. Tomatoes also contain folates [24,26], which play an important role in the lowering of homocysteine levels and therefore CVD risk [27]. The beneficial effects of tomato juice are a result of the interactions among different compounds and could be increased by the addition of other functional ingredients, which could have a synergistic effect with the existing natural components.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to stage 1, total folate is increased about 4 fold (from 31 g/100 g to 156 g/100 g) in stage 6. Early studies have reported changes in folate levels during fruit ripening in tomatoes, strawberries and papayas (22,(31)(32)(33). There are two studies investigating the folate level in several cultivars of tomatoes during ripening which fi nd a decrease of folate content when comparing the mature green and fully ripened stages for most cultivars (31,33).…”
Section: Comparison Of the Distribution Of Folate Species And Total Fmentioning
confidence: 99%